PENERAPAN PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA KELAS VIII B SMP NEGERI 2 PETERONGAN - M. SIDIK (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
This research is a Classroom Action Research (CAR) which aims to describe the application of constructivism learning that can increase teacher activity, student activity and science learning outcomes in the material of motion systems in plants for class VIII B students of SMP Negeri 2 Peterongan, Jombang Regency. PTK was chosen because the problem to be solved comes from the classroom learning process carried out by the teacher. The subjects in this study were class VIII B students in the odd semester of the 2022/2023 academic year with a total of 31 students consisting of 16 boys and 15 girls. This research was conducted in two cycles, each cycle consisting of four stages, namely planning , implementation, observation and reflection. The results of this study were: (1) Teacher activity increased, with observations that were originally 84.4% in cycle I increased to 89.4% in cycle II. (2) The activity of students increased, with the results of observations in the first cycle which was 70% and in the second cycle it became 81.4%. (3) The students' science learning outcomes increased with the percentage of classical mastery of learning outcomes obtained in the first cycle of 71.9% and in the second cycle it increased to 87%. Based on the results of the study it can be concluded that constructivism learning can increase teacher activity, student activity and learning outcomes. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk mendeskripsikan penerapan pembelajaran konstruktivisme yang dapat meningkatakan aktivitas guru, aktivitas peserta didik dan hasil belajar IPA materi sistem gerak pada tumbuhan peserta didik kelas VIII B SMP Negeri 2 Peterongan Kabupaten Jombang. PTK dipilih karena masalah yang akan dipecahkan berasal dari proses pembelajaran kelas yang dilakukan oleh guru. Subyek dalam penelitia ini adalah peserta didik kelas VIII B semester ganjil tahun pelajaran 2022/2023 dengan jumlah peserta didik 31 orang terdiri dari 16 laki – laki dan 15 perempuan.Penelitian ini dilakukan dalam dua siklus yang masing – masing siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi dan refleksi. Adapun hasil dari penelitian ini adalah: (1) Aktivitas Guru meningkat, dengan hasil observasi yang semula 84,4% pada siklus I meningkat menjadi 89,4% pada siklus II. (2) Aktivitas peserta didik meningkat, dengan hasil observasi pada siklus I yang semula 70% dan pada siklus II menjadi 81,4%. (3) Hasil belajar IPA peserta didik meningkat dengan persentase ketuntasan klasikal hasil belajar yang diperoleh pada siklus I sebesar 71,9% dan pada siklus II meningkat menjadi 87%. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembelajaran kontruktivisme dapat meningkatkan aktivitas guru, aktivitas peserta didik dan hasil belajar.